PERLINDUNGAN KONSUMEN TERHADAP NASABAH ATAS PENYIMPANAN BARANG DI SAFE DEPOSIT BOX (STUDI PADA PT. BANK PANIN CABANG PEMBANTU TEBING TINGGI) - Wahyu Simon Tampubolon; Sunarmi Sunarmi; Hasim Purba; Utari Maharany Barus (USU LAW JOURNAL, 2014)
ABSTRACT Safe Deposit Box Service is a kind of services of lending a storage box for property orsecurities which is specifically designed from the materials steel and placed in a space that is sturdy and fireproof for maintaining the security of the things and providing a sense of security for its users. Generally, the items that are stored in a safe deposit box has a high material value and very important for the customers of safe deposit box. Since the interest of people to use the safe deposit boxis high, it is a need to have any rules that protects the customers of safe deposit boxagainst the losses in case of lost or destruction of things stored in the safe deposit box. The bank must provide liability related to the lost or destructions of the thingsstored in the safe deposit box offered by the bank, and also it is a needed to have a special ruleswhich regulating the safe deposit box facilities as well as the resolving disputes related to the used of safe deposit box facilities, so there is a legal form of protection which can be a legal umbrella for the customer and the bank since both parties have a balanced position. Therefore there will be no aggrieved parties associated to the storage agreement of safe deposit box.